Small intestinal bacterial overgrowth – current, novel and possible future methods of treatment and diagnosis - Sobczyk, Mateusz; Porzak, Mikołaj; Żuraw, Daria; Sodolska, Alicja; Oleksa, Paulina; Jasiński, Kacper (Prospects in Pharmaceutical Sciences, 2024)
Small intestinal bacterial overgrowth (SIBO) is a prevalent issue, frequently overlooked in clinical practice. Its prevalence is unknown because SIBO requires diagnostic testing, however, in most studies, SIBO has been detected anywhere from <2% to 22% of healthy controls. Breath tests, which detect the presence of hydrogen in exhaled air, are the most used diagnostic method. However, their low sensitivity and specificity indicate the need for research into new more accurate methods. The standard treatment is antibiotic therapy with rifaximin. After antibiotic therapy, there is a risk of recurrence and the emergence of multidrug-resistant bacterial strains. Recurrence ratio after antibiotic therapy have been documented in 12.6% of patients after 3 months, 27.5% after 6 months and 43.7% after 9 months. There are promising results from studies on the use of probiotics and herbal preparations in treatment, but these studies have been conducted on relatively small groups of patients. This indicates the need for multicentre randomised trials with large numbers of patients to develop effective methods for the diagnosis and treatment of SIBO.